The Authority of the Classification Committee in the Conformity Test of the Online Game "Grand Theft Auto V" Based on the Minister of Communication and Information Regulation Number 11 of 2016 concerning Classification of Electronic Interactive Games - Prianggih, Ryan; Jazuli, H.E. Rakhmat; Citrawan, Ahmad Lanang (Beleid, 2023)
One of the problems related to the use of digital technology that has no boundaries in its use is the presence of an entertainment media in the form of electronic games, which in its content contains harmful elements if it can be accessed freely by children on the internet. There needs to be supervision by the government in handling policies regarding the classification of games in Indonesia, because Indonesia has unique customs and cultural values that are not owned by other countries in the world. How is the authority exercised by the Classification Committee in testing the suitability of game classification results in Indonesia. In addition, the theories used are the theory of authority and the theory of supervision. This research uses a research method that is empirical juridical. The research specification used is descriptive analytical. The research data sources used are primary and secondary data. Data collection techniques used in this research. This research uses field research techniques, library research. Data analysis in the research used is descriptive qualitative approach. The result of the research is an age game rating logo policy that is not in accordance with the rule of law (das sollen and das sein). Conclusion based on the Regulation of theMinister of Communication and Information Technology Regulation Number 11 of 2016 concerning Classification of Electronic Interactive Games, that the Classification Committee in carrying out the authority to test the suitability of online game classification results is to carry out a testing process related to age game ratings in accordance with the age classification applied through the game rating logo provided through the classification registration process through the IGRS policy (Indonesian Game Rating System). Supporting factors in the authority of the Classification Committee. Classification Committee's authority in the form of support from the Directorate General of APTIKA's Work Team, the existence of a plan for international cooperation, adequate facilities and facilities. While the inhibiting factors are legislation and society Suggestions. expected, namely an evaluation related to the legal provisions contained in the regulation so that it is binding, has obligations and sanctions. Adjust the flow of authority between structural and functional positions of the Classification Committee.